Investigating role of IL-4 receptor alpha (IL-4Ra) in murine models of atopic dermatitis - Scibiorek, Martyna (Department of Clinical Laboratory Sciences, 2023)
Atopic dermatitis (AD) is a common pruritic inflammatory skin disease with complex environmental and genetic predisposition factors. Primary skin barrier dysfunction and aberrant T helper 2 (TH2) responses to common allergens, together with increased serum IgE antibodies, characterise the disease. B and T cells are essential in the disease manifestation, however, the exact mechanism of how these cells are involved in skin sensitization to allergens is unclear. Clinical studies investigating the efficacy of monoclonal antibody to IgE such as omalizumab and ligelizumab do not show efficacy in AD patients. However, targeting IL-4/IL-13 signalling axis with dupilumab show efficacy in AD. We investigated the importance of interleukin 4 receptor alpha (IL- 4Rα) signalling specifically on B and T cells to understand the requirement of this signalling axis in epicutaneous skin sensitisation during AD. We investigated 3 models of AD using House dust mite (HDM), Ovalbumin (OVA) and low-calcemic analog of vitamin D (MC903) on mouse strains lacking IL-4Ra on various B and T cells. We used mb1creIL-4Rα-/lox (mice lacking IL-4Rα on B cells), iLcKCre IL-4Rα-/lox (mice lacking IL-4Rα on all T cells), LcKCre IL-4Rα-/lox (mice lacking IL-4Rα on CD4+ and CD8+ T cells), CD4Cre IL-4Rα-/lox (mice lacking IL-4Rα on CD4+ Tcells), Foxp3Cre IL-4Rα-/lox (mice lacking IL-4Rα on Foxp3+ T regulatory cells) and IL-4Rα-/lox littermate controls. We analysed cellular infiltrate in the skin and inguinal lymph nodes (LN) by flow cytometry, histology of the skin, serum antibodies and cytokines by ELISA. Mice lacking IL-4Rα-responsive B cells showed a reduced serum IgE levels, but no significant differences in epidermal thickening compared to littermate control in HDM or MC903 models. Mice investigated in the T cell arm of the study showed reduced epidermal thickening in pan-T cell IL-4Rα knock-out, but not in groups lacking IL-4Rα signalling in adaptive T cells, suggesting importance of IL4/IL13 signalling axis in ydT cells during AD. Overall, our results suggest that deletion of IL-4Rα on innate T cells regulates inflammatory response in atopic dermatitis.